2009
DOI: 10.2215/cjn.05560809
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in Online Hemodiafiltration and High-Flux Hemodialysis

Abstract: Conclusions: We found no benefits of HDF over high-flux HD with respect to anemia management, nutrition, mineral metabolism, and BP control. The mortality benefit associated with HDF requires confirmation in large randomized, controlled trials. These data may contribute to their design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
101
3
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 37 publications
11
101
3
9
Order By: Relevance
“…There is increasing interest in techniques that maximize middle-molecule clearance, such as hemodiafiltration (HDF) (14,15). Clearance of these molecules may be an important marker of adequate treatment in both peritoneal dialysis (10,16) and hemodialysis (HD) (11,17).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in techniques that maximize middle-molecule clearance, such as hemodiafiltration (HDF) (14,15). Clearance of these molecules may be an important marker of adequate treatment in both peritoneal dialysis (10,16) and hemodialysis (HD) (11,17).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Several nonrandomized observational studies suggested a survival benefit in patients who are treated with online hemodiafiltration. [8][9][10][11] However, small randomized studies failed to show a difference between online hemodiafiltration and standard hemodialysis (as summarized by van der Weerd et al 12 ). On the basis of the above-mentioned theoretical considerations, the absence of conclusive clinical data, and the growing interest in convective techniques, the Convective Transport Study (CONTRAST) was initiated (ClinicalTrials.…”
mentioning
confidence: 99%
“…E. Vilar с соавт. (626 пациентов на ВПГД, 232 -на ГДФ) сообщают, что по резуль-татам мультивариантного анализа, преимуществен-ное лечение ГДФ (>50% проведенных процедур) являлось статистически значимым независимым предиктором снижения риска смерти, по сравне-нию с преимущественным лечением ВПГД [16]. В исследовании J. Vinhas с соавт.…”
Section: влияние на смертностьunclassified
“…Vilar с соавт. также отмечают, что эпизоды ИДГ были более частыми у пациентов при лечении ВПГД, чем при лечении ОЛ-ГДФ (0,05/ процедуру против 0,03/процедуру, p < 0,001) [16]. Особый интерес представляют данные ретроспек-тивного исследования, проведенного F.G. MoraBravo с соавт.…”
Section: улучшение гемодинамической стабильностиunclassified